2023
DOI: 10.5937/zasmat2303274n
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of mild steel corrosion by papaya and neem extracts

Agha Ndukwe,
Dan Etim,
Anaele Uchenna
et al.

Abstract: This study examined earlier research on using papaya and neem extracts as inhibitors to minimize the corrosion of mild steel in a variety of corrosive situations. The potential inhibitory characteristics of plant extracts to potentially replace the hitherto used, well-known inhibitors that are harmful to the people handling them as well as the environment, inspired several scholars to conduct corrosion inhibition tests on metals using plant extracts. The findings of earlier research demonstrated that the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The Freundlich adsorption isotherm may be used to define an exponential energy distribution that surrounds a heterogeneous surface [48,49]. It gives a clear explanation of the relationship between the inhibitor concentration in a liquid that is in touch with a metal's surface and inhibitor concentration there.…”
Section: Freundlich Adsorption Isothermmentioning
confidence: 99%
See 2 more Smart Citations
“…The Freundlich adsorption isotherm may be used to define an exponential energy distribution that surrounds a heterogeneous surface [48,49]. It gives a clear explanation of the relationship between the inhibitor concentration in a liquid that is in touch with a metal's surface and inhibitor concentration there.…”
Section: Freundlich Adsorption Isothermmentioning
confidence: 99%
“…It gives a clear explanation of the relationship between the inhibitor concentration in a liquid that is in touch with a metal's surface and inhibitor concentration there. The Freundlich adsorption isotherm model's mathematical formulation is as follows [48]:…”
Section: Freundlich Adsorption Isothermmentioning
confidence: 99%
See 1 more Smart Citation
“…Paper is available on the website: www.idk.org.rs/journal In general, the menace of corrosion refers to the degradation of materials occasioned by electrochemical or chemical reactions. Unlike ceramics, metals tend to degrade in acidic environments and previous studies have shown that the corrosion of metals can be deterred in various acidic media using different plant extracts and pastes [4][5][6][7][8][9][10][11][12][13]. When exposed to acidic conditions, ceramics display improved corrosion resistance in comparison with metals [14].…”
Section: Introductionmentioning
confidence: 99%